Self‐Assembly of Measles Virus Nucleocapsid‐like Particles: Kinetics and RNA Sequence Dependence. Issue 32 (6th June 2016) - Milles, Sigrid; Jensen, Malene Ringkjøbing; Communie, Guillaume; Maurin, Damien; Schoehn, Guy; Ruigrok, Rob W. H.; Blackledge, Martin
Abstract: Measles virus RNA genomes are packaged into helical nucleocapsids (NCs), comprising thousands of nucleo‐proteins (N) that bind the entire genome. N‐RNA provides the template for replication and transcription by the viral polymerase and is a promising target for viral inhibition. Elucidation of mechanisms regulating this process has been severely hampered by the inability to controllably assemble NCs. Here, we demonstrate self‐organization of N into NC‐like particles in vitro upon addition of RNA, providing a simple and versatile tool for investigating assembly. Real‐time NMR and fluorescence spectroscopy reveals biphasic assembly kinetics. Remarkably, assembly depends strongly on the RNA‐sequence, with the genomic 5′ end and poly‐Adenine sequences assembling efficiently, while sequences such as poly‐Uracil are incompetent for NC formation. This observation has important consequences for understanding the assembly process. Abstract : Self‐organization of the measles virus nucleoprotein into nucleocapsid‐like particles was observed upon simple addition of RNA, allowing investigation of the nucleocapsid assembly process. Real‐time NMR and fluorescence spectroscopy revealed biphasic assembly kinetics and demonstrate that assembly depends strongly on RNA sequence.